Goal Attribution toward Non-Human Objects during Infancy Predicts Imaginary Companion Status during Preschool Years - Moriguchi, Yusuke; Kanakogi, Yasuhiro; Todo, Naoya; Okumura, Yuko; Shinohara, Ikuko; Itakura, Shoji (Frontiers in Psychology, 2016)
It has been shown that there is a significant relationship between children’s mentalizing skills and creation of an imaginary companion (IC). Theorists have proposed that interaction with an IC may improve mentalizing skills, but it is also possible that children’s mentalizing skills affect their creation of an IC. In this longitudinal study, we examined whether goal attribution in infants younger than 1 years old (Time 1) predicted their creation of ICs at 48 months old (Time 2). At Time 1, infants’ goal attribution was measured in an action prediction experiment, where infants anticipated three types of action goals: 1) another person’s goal-directed action (GH condition); 2) another person’s non-goal-directed (BH condition); and 3) a mechanical claw’s goal-directed action (MC condition). At Time 2, parents completed questionnaires assessing whether their children had ICs. The path analyses using Bayesian estimation revealed that infants’ anticipation in the MC condition, but not in the GH and BH conditions, predicted their later IC status. These results indicate that infants’ goal attributions to non-human agents may be a strong predictor of their later IC creation. Early mentalizing skills toward non-human objects may provide children with a basis for their engagement in imaginative play.